Routing Model of Oil Palm Fibre Waste toward Gas Fuel Production Supply Chain Management: Malaysia Industry - Zakaria, Izatul Husna; Ibrahim, Jafni Azhan; Othman, Abdul Aziz (International Journal of Supply Chain Management, 2017)
Green energy is becoming an important aspect for developed countries in the world toward energy security by reducing dependence on fuel import and enhancing better life quality by living in sustainable healthy environment. Issues regarding renewable energy production are source sustainability and reliability to ensure continuous production. Palm oil operation produces 80% varies type of waste and 20% oil palm products. Different range of physical and chemical of palm oil waste properties request different particular treatment and conversion energy method to optimize the desired bio product. Aim of this paper is to suggest the best Routing Model of Palm Oil Fibre Waste toward Gas Fuel Production Supply Chain Management based on evaluation of current Malaysia’s palm oil industry, practices in palm oil waste treatment and available energy conversation technologies. The framework is based on palm oil mill operation to utilise annually solid waste generated as source for stable annual biogas electricity production for grid. This paper highlight framework for the prospective researchers as well as practitioners to do further research to optimizes utilisation of palm oil waste for electricity production.